An algorithm to estimate speed by colour–based object detection. (30th December 2014) - Shavalipour, Aghil; Haris, Sallehuddin Mohamed
This paper describes a method to determine the travelling speed of a moving object from a sequence of captured video image frames. Using a new method for the detection of objects in colour images, the target moving object is identified and located in each video frame. The object detection process is performed by a colour segmentation method and a labelling algorithm. By defining a rectangular bounding box around it in every frame, the detected object image is isolated from other moving objects in the video, and tracked. The velocity can then be determined by calculating the distance through which the bounding box centroid moves over a sequence of frames with respect to the frame rate of the video recording.